National Vascular Registry Report on surgical outcomes and implications for vascular centres. Issue 6 (31st March 2014) - Sidloff, D. A.; Gokani, V. J.; Stather, P. W.; Choke, E.; Bown, M. J.; Sayers, R. D.
<x xml:space="preserve">Abstract</x> Background The National Vascular Registry Report on Surgical Outcomes (NVSRO) coincided with the update of the National Health Service Standard Contract for Specialized Vascular Services in Adults (NHSSCSVS). The latter promises patients minimum standards for vascular centres. The present study aimed to determine whether current data support the standards proposed in the NHSSCSVS. Methods Numbers of abdominal aortic aneurysm (AAA) repairs and carotid endarterectomies (CEAs) performed by hospital Trust and surgeon, and their outcomes were obtained from the NVRSO. These were assessed against NHSSCSVS recommendations that included: more than 60 AAA repairs per year per Trust, over 50 CEAs per year per Trust and at least six vascular surgeons per Trust. Results Based on NVRSO data, 107 hospital Trusts (92·2 per cent) would fail to meet the minimum standards required to achieve vascular centre status. Outcomes were poorer in these hospitals (overall mortality rate after AAA: 2·7 versus 1·3 per cent; P = 0·007). There were strong associations between number of AAA repairs or CEAs per Trust and better outcomes (AAA repair, P < 0·001; CEA, P = 0·004). These remained significant when analysed by individual surgeon (AAA repair, P < 0·001; CEA, P < 0·001). Trusts undertaking 60 or fewer elective AAA repairs per year had significantly higher elective AAA mortality rates (2·7 versus 1·7 per cent; P = 0·010). Trusts performing a minimum of 50 CEAs per year had significantly lower perioperative mortality/morbidity rates (1·9 versus 3·0 per cent; P = 0·032). Trusts with seven or more surgeons demonstrated lower AAA‐related mortality rates (1·7 versus 2·7 per cent; P = 0·018). Conclusion Data from the NVRSO suggest that the majority of hospital Trusts presently fail to meet the standards for vascular centre status. NVRSO data support a standard of more than 60 elective AAA repairs and 50 CEAs per Trust per year. A minimum of seven vascular surgeons per unit was associated with better outcomes. These data support the ongoing remodelling of vascular services in the UK.